When Diamond is Still a Luxury: An Early Career Researcher Perspective - Liu, Meng (Dutch Journal of Applied Linguistics, 2024)
In this response to Diamond is a scientist’s best friend, Meng Liu explores why Diamond open access is still a luxury for early career researchers (ECRs), evaluates potential responses to this dilemma, and advocates empowering ECRs through grassroots communities to promote open scholarship.